Development of electro-fenton techniques for the oxidation of hazardous aqueous pollutants - Colades, James I.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
This dissertation was focused on developing simple electro-Fenton techniques to improve the degradation efficiency of organic pollutants in water. The whole study is divided into three parts: (i) modeling the electrochemical dosing of iron, (ii) packed-bed electrode configuration using reticulated vitreous carbon (RYC) as packing material for in-situ generation of H2O2 and (iii) dual-power supply electro-Fenton configuration for independent electrochemical H2O2 generation and iron dosing. The iron dosing model using time and applied current as independent variables was successfully implemented with residuals not exceeding 0.10 mM Fe. The model was also used to employ several dosing modes on the degradation of methylene blue (MB). Single and continuous dosing were also compared in terms of color, TOC and COD removal with MB as target pollutant. The packed bed electrode configuration using RYC chips as packing material was shown to successfully generate H,O, from oxygen supplied from sparged air. The system was also used to degrade p-nitrophenol (pnP) where extent of degradation was studied by COD, TOC, and intermediate analysis using GC-MS. Finally, dual power supply for the independent electrochemical H2O2 generation and iron dosing as sacrificial anode was studied using ME as target pollutant. The electrochemical generation of H2O2 was done using activated carbon fiber as cathode in a packed-bed configuration. This studies conducted shows that: (i) iron dosing for Fenton applications can be modeled as a function of time and applied current, (ii) an RYC packed-bed electrode configuration was able to electrochemically generate H20, and degrade pnP, and (iii) the dual-power supply configuration provided dosing control of both iron and H20, for successful degradation of ME. The results of this study shows the promising application of the electro-Fenton technology for the chemical-free treatment of organic and recalcitrant pollutants in wastewater.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman
Keywords: Electrolytic oxidation; Water -- Purification